If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + 60 = 9x + 36 Reorder the terms: 60 + 17x = 9x + 36 Reorder the terms: 60 + 17x = 36 + 9x Solving 60 + 17x = 36 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 60 + 17x + -9x = 36 + 9x + -9x Combine like terms: 17x + -9x = 8x 60 + 8x = 36 + 9x + -9x Combine like terms: 9x + -9x = 0 60 + 8x = 36 + 0 60 + 8x = 36 Add '-60' to each side of the equation. 60 + -60 + 8x = 36 + -60 Combine like terms: 60 + -60 = 0 0 + 8x = 36 + -60 8x = 36 + -60 Combine like terms: 36 + -60 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 5/24=10/g | | 4/9a=1/9a-5/6 | | 5n-6=-106 | | 14x-76=8x-40 | | -6x-28=-3x-16 | | 0.09xX=72.44 | | -18x-83=-12x-47 | | -8x+32=-5x+17 | | h-6.5=15.2 | | 4y-3x=-84 | | -5x+26=-3x+16 | | 52=w/4 | | 9x+36=6x+18 | | F(x)=-1(x+1)(x-7) | | 3x+37=11.25 | | -18x+31=-12x+19 | | cos70=14/x | | 48-4x=7x | | 2-(x+1)=2x-11 | | 6(3x-2)=3-2(4x+1) | | -9x+9=-6x+6 | | m/2=27 | | 7x+4=7(8)+4 | | 6(w-2)=-7w-25 | | 19x-79=12x-44 | | 8(-2x+3)=32 | | 80-2x=50 | | x-.3x=38000 | | -15x-125=-9x-83 | | -3k^2=-75 | | 6a^2-8ab=0 | | -4x+14y=2 |